HUBUNGAN ANTARA KADAR ENZIM GLUTATION REDUKTASE DENGAN DERAJAT KEKERUHAN INTI LENSA - Sulistya, T Budi; Dewi, Debby Shintiya; Suyuti, Hidayat; Sumarno, Sumarno (Jurnal Kedokteran Brawijaya, 2006)
The aim of this study was to determine the correlation between the level of glutathione reductase [GR] in relation with the severity of nuclear cataract and the increase of age. An analytic cross sectional observasional study  of nuclear cataract patient seen at Saiful Anwar Hospital and Mass Cataract Surgery performed by Perdami Malang was carried out. Patients were classified into 3 groups based on ageand 4 groups based on severity of nuclear cataract. The samples were taken by consecutive sampling and were operated on visual indication. The extracted lens were examined for [GR]. The laboratory findings of [GR] were compared with the severity of senile cataract. The data were analyzed with one way ANOVA. Confidence limit was set at 95%. A total of  55 patients were included with the sample size in 40-50 age group less than estimation. The [GR] were found to be significanfly lower in the older age (p=0,01) and the more severe cataract groups (p=0,00). The [GR] were also found to be significantly decreased with the increase of cataract severity in 40-50 age group (p=0,00), 50-60 age group (p=0,01) and >60 age group (p=0,00). In the grade 2 cataract, there were no significant difference of [GR] between age group (p=0.22). This also occured in grade 3 (p=0.23) while  in the grade 4, there were significant difference between age group (p=0.01). This also occured in grade 5 (p=0.06).